Single transistor high linearity and wide dynamic range active inductor. (4th July 2013) - Leuzzi, G.; Stornelli, V.; Pantoli, L.; Del Re, S.
Summary In this paper, an active inductor (AI) with high linearity and high dynamic range, including a minimum number of components, is presented. The AI is composed by a single transistor, and by a passive compensation network; the latter allows the control of the values of both the inductance and the series resistance. In order to show the feasibility of the proposed AI for filter applications, a prototype board on a TLX8 substrate with a first‐order active band‐pass filter has been fabricated and tested. The filter has a center frequency of 2470 MHz (useful for Bluetooth applications) and a measured noise figure (NF) of 9 dB with a −5 dBm P1dB compression point, and a 75 dB dynamic range. Copyright © 2013 John Wiley & Sons, Ltd.